Impact Of Remittances On Foreign Currency Supply In Developing Economies: A Case Of Zimbabwe From 2009 to 2022 - Chikwira, Collin (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The study investigates the impact of remittances on the foreign currency supply in Zimbabwe from 2009 to 2022. The analysis focuses on understanding how remittance inflows have contributed to the availability of foreign currency in the Zimbabwean economy, considering the economic challenges the country has faced, including hyperinflation, currency devaluation, and economic instability. The Ordinary Least Squares (OLS) regression method was employed to analyse Zimbabwe’s relationship between remittances and foreign currency supply. The study uses annual data from 2009 to 2022. The OLS regression results indicate a significant positive relationship between Zimbabwe’s remittances and foreign currency supply. The analysis reveals that remittances have been a crucial foreign currency source, helping stabilise the economy during economic turmoil. Additionally, exchange rates and GDP significantly impact the foreign currency supply. The findings underscore remittances’ vital role in enhancing Zimbabwe’s foreign currency supply. Given the economic instability in the country, remittances have served as a reliable and stable source of foreign exchange, which is critical for sustaining economic activities. This study contributes to the literature on remittances and their economic impact by providing empirical evidence from Zimbabwe. It highlights the importance of fostering policies encouraging remittance inflows, which can significantly stabilise foreign currency supply in developing economies facing economic challenges.